Digital literacy of healthcare professionals in pharmacies - Andric, Sanja; Odalović, Marina (Archives of Pharmacy, 2022)
Professional standards require from healthcare professionals to possess a certain level of digital literacy. The aims of paper were: examination of the experience of healthcare professionals in pharmacies in the use of digital technologies, self-assessment of knowledge and skills, evaluation of attitudes and analysis of the needs for improvment of digital competencies. A special paper questionnaire was designed and used in the research, which was distributed to the pharmacy staff from AU “Benu“. 94,3% use digital technology at work every day, 89,8% of respondents using it for searching of medical and medicine information (89,8%). Only 9,7% of the respondents completed an additional formal program or course. Pharmacists assessed their digital literacy significantly higher than pharmaceutical technicians, 3,67±0,79 vs 3,44±0,63 (p<0,05). Most of them think that it is important to improve their digital literacy (agreement 4,62±0,95) and are motivated to do so through additional training or learning on their own (agreement 4,50±0,94). They understand benefits of new ways of communicating and data source and spontaneously accept the new technologies in the field of eHealth. A similar conclusion is mentioned in National strategy for digital skills development. Pharmacy professionals rate their digital literacy at 3,56, which could be compared with similar research from Canada, where computer literacy is mostly rated at 3. Considering the positive attitude towards using digital technologies in practice and high motivation for improving digital skills, it is expected that the pharmacists will quickly master technological innovations in the field of providing pharmaceutical services in the future.